Análise comparativa entre as propriedades do gesso obtido de rejeito da produção de sal e gesso comerciais - Costa, Juliana Elionara Bezerra (2013)
The environmental impacts, caused by the solid residues generation, are an often quoted concern nowadays. Some of these residues, which are originated from different human activities, can be fully reused, reducing the effects of the poor waste management on the environment. During the salt production process, the first formed crystals are discarded as industrial waste. This is mainly made of gypsum that is a calcium sulfate dihydrate (CaSO4.2H2O). The gypsum in question may go through a calcination process due to the plaster (CaSO4.0,5H2O) production and then the application on the cement industry. Considering the necessity of development and application for these industrial wastes, this paper aims to analyze the plaster, called Salgesso, from the gypsum that was generated during the salt production, and its use viability on the civil construction industry in order to create environmental and economical benefits. For characterization, the following experiments were performed: X-ray Fluorescence (XRF), X-ray Diffraction (XRD), thermal analysis (TG/DTG) and Scanning Electron Microscopy (SEM) with EDS. The following tests were also performed to obtain the mechanical characteristics: Thinness Modulus, Unit Mass, Setting Time and Compressive Resistance. Three commercial plasters used on civil construction were taken as references. All of these tests were performed according to the current standards. It was noticed that although there were some conflicting findings between the salt and commercial plasters in all of the studied properties, the Salgesso has its values within the standard limits. However, there is the possibility to improve them by doing a more effective calcination process. Three commercial plasters, used in construction, were used as reference material. All tests were performed according to standards in force. It was observed that although some tests present conflicting findings between the salt and gypsum plasters commercial properties in all of the studied Salgesso have values within the limits imposed by the standard, but can be improved simply by calcination process more effective